Effect of cellulose nanofibers and acetylated cellulose nanofibers on the properties of low‐density polyethylene/thermoplastic starch blends. Issue 8 (17th May 2018) - Ahmadi, Mobina; Behzad, Tayebeh; Bagheri, Rouhollah; Heidarian, Pejman
Abstract: The aim of this study was to evaluate the effect of cellulose nanofibers (CNFs) and acetylated cellulose nanofibers (ACNFs) on the properties of low‐density polyethylene/thermoplastic starch/polyethylene‐grafted maleic anhydride (LDPE/TPS/PE‐ g ‐MA) blends. For this purpose, CNFs, isolated from wheat straw fibers, were first acetylated using acetic anhydride in order to modify their hydrophilicity. Afterwards, LDPE/TPS/PE‐g‐MA blends were reinforced using either CNFs or ACNFs at various concentrations (1–5 wt%) with a twin‐screw extruder. The mechanical results demonstrated that addition of ACNFs more significantly improved the ultimate tensile strength and Young's modulus of blends than addition of CNFs, albeit elongation at break of both reinforced blends decreased compared with the neat sample. Additionally, biodegradability and water absorption capacity of blends improved due to the incorporation of both nanofibers, these effects being more pronounced for CNF‐assisted blends than ACNF‐reinforced counterparts. © 2018 Society of Chemical Industry Abstract : We imparted higher biodegradability and mechanical properties to LDPE by blending thermoplastic starch and adding modified CNFs with the LDPE matrix.